Integrated chemical, technology & equipment process knowledge management system based on risk based process safety - Nur Izzati, Pakhor Anuar; Hanida, Abdul Aziz; Razali, Ahmad (IOP Publishing, 2019)
Major accidents in the industry such as fire, gas explosion, and unexpected toxic gas release are continuously reported worldwide. Lacking Process Knowledge Management (PKM) and failure to update and access the information was identified as one of the contributing factors. One of the established elements that intended to minimize this issue is PKM. However, lacking a systematic system to implement the PKM program has hindered the improvement of process safety level at workplace. The study focuses on development of PKMS database based on Risk Based Process Safety (RBPS) guideline. PKMS was developed by using Plan-Do-Check-Act (PDCA) concept. Validation of system was conducted through inserting real plant data from two chemical plants and feedback from process safety expert for further improvement. The developed PKMS allows the end user to store, review, modify and update the data regarding hazardous chemicals, technology and equipment information that involve with the operation. PKMS emphasis hazards related with the process in systematic ways thus minimizing potential incomplete control of hazard. PKMS interfaces allows management to do a self-check audit and helps the management to track the information. As leading indicator, PKMS allows the user to review overall status of the company compliance to the safety standard.